Play-Based Strategies for Speech Therapy and Vocal Health Face-to-Face and Distance Learning Actions for Children Distance Learning Actions for Children: An Integrative Literature Review - de Oliveira, Amanda Gabriela [UNESP]; Fabbron, Eliana Maria Gradim [UNESP] (Elsevier, 2021)
Introduction: Diversifying voice therapy strategies is critical to get children and adolescents to adhere to the therapeutic process. Purpose: To investigate the face-to-face and distance playful strategies have been used for vocal health education and voice therapy in children and adolescents. Methods: An integrative literature review was carried out based on the recommendations of the Preferred Reporting Items for Systematic Reviews and Meta-Analyzes (PRISMA). A search for full texts was conducted on the Virtual Health Library, Scientific Electronic Library Online (SCIELO) and PuBMed databases using the following descriptors, and their corresponding Medical Subject Headings (MeSH): voice (voz); voice quality (qualidade da voz); dysphonia (disfonia); voice disorders (distúrbios da fala); voice training (treinamento da voz); telemedicine (telemedicina); therapeutics (terapêutica); health promotion (promoção da saúde); group practice (prática de grupo); recreation therapy (terapia recreacional); child (criança); preschool (pré-escolar) and adolescent (adolescente). Results: After full reading of the studies, 15 articles were included and categorized into the following topics: face-to-face and distance playful strategies for voice therapy in children; playful strategies with gamification for education and for voice therapy in children; and vocal health educational actions in children. Conclusion: The study found a higher number of studies that carried out educational actions and playful strategies, while fewer studies were related to the production of materials, gamification and online services for voice therapy in children. Given the proven benefits of this strategy for children, further studies focusing on the development and application of playful strategies, such as the use of gamification, should be conducted in order to stimulate the skills and adherence of this population to therapy.
Keywords: Child; Dysphonia; Recreation therapy; Voice; Voice training